2009
DOI: 10.1177/0148607108328470
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Supplementation in Adult Nutrition Therapy: Practical Considerations

Abstract: Preexisting micronutrient (vitamins and trace elements) deficiencies are often present in hospitalized patients. Deficiencies occur due to inadequate or inappropriate administration, increased or altered requirements, and increased losses, affecting various biochemical processes and resulting in organ dysfunction, poor wound healing, and altered immune status with deleterious sequelae. Guidelines for the 13 essential vitamins and 10 essential trace elements have been established. These recommendations, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
133
2
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(143 citation statements)
references
References 100 publications
1
133
2
7
Order By: Relevance
“…maintenance dosing guidelines, about 38% of serum selenium concentrations were below normal in SBS and non-SBS patients alike. Although a minimum selenium dose of 50 mcg/d and a usual dose of 60 mcg/d have been recommended in PN, 15,17 our data show that even a higher parenteral selenium dose of about 70 mcg/d achieved normal serum selenium concentrations in only about 60% of cases. Higher maintenance selenium doses of 60-100 mcg/d have been actually suggested for adult home PN patients, and patients with selenium depletion may require even higher doses.…”
Section: Seleniummentioning
confidence: 58%
See 1 more Smart Citation
“…maintenance dosing guidelines, about 38% of serum selenium concentrations were below normal in SBS and non-SBS patients alike. Although a minimum selenium dose of 50 mcg/d and a usual dose of 60 mcg/d have been recommended in PN, 15,17 our data show that even a higher parenteral selenium dose of about 70 mcg/d achieved normal serum selenium concentrations in only about 60% of cases. Higher maintenance selenium doses of 60-100 mcg/d have been actually suggested for adult home PN patients, and patients with selenium depletion may require even higher doses.…”
Section: Seleniummentioning
confidence: 58%
“…17,29 The majority (92.6%) of manganese doses far exceeded the upper limit of A.S.P.E.N. supplementation guidelines.…”
Section: Manganesementioning
confidence: 99%
“…Copper, manganese and iron levels significantly increased when the bars were supplemented with 10%, 15% or 20% of jerivá flour. Micronutrients are compounds necessary for proper physiological condition of the body which can be orally administered in enteral or parenteral diet, and are required to maintain a proper balance of nutrients (Davidi et al, 2011;Sriram & Lonchyna, 2009). Because minerals cannot be synthesized, they should be supplied from food, and considering the mineral deficiencies worldwide, the bars developed with jerivá flour can be considered as viable alternatives for mineral intake.…”
Section: Resultsmentioning
confidence: 99%
“…However, these measures are of limited significance to reflect accurate trace element status in critical illness. Measuring serum levels of trace elements is difficult and requires careful collection techniques, using special trace elementfree tubes [3]. Previous balance studies have demonstrated the unreliability of serum trace element levels [4].…”
Section: Assessment Of Trace Element Status In the Critically Ill Patmentioning
confidence: 99%
“…Iron plays a central role in oxygen transport as the key component of the heme molecule and also other oxygen-carrying proteins including heme enzymes, myoglobin, and cytochrome a-a 3 . As a constituent of the functional groups of many enzymes operating in the Krebs cycle, it is essential for energy metabolism.…”
Section: Ironmentioning
confidence: 99%